2022
DOI: 10.1021/acs.biomac.2c00484
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hydration Water Bound to Choline Phosphate-Containing Polymers

Abstract: Zwitterionic methacrylate polymers with either choline phosphate (CP) (poly(MCP)) or phosphorylcholine (PC) (poly(MPC)) side groups were analyzed to characterize the bound hydration water molecules as nonfreezing water (NFW), intermediate water (IW), or free water (FW). This characterization was carried out by differential scanning calorimetry (DSC) of polymer/water systems, and the enthalpy changes of cold crystallization and melting were determined. The electron pair orientation of CP is opposite to that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Since the local hydration efficiency of the charges in the zwitterions is independent on the zwitterion species, water is involved in each phase at the high concentration stage. [ 34 ] However, once the water content is above the water capacity of the PSB4 phase, water is subjected to partition selectively to the PCB2 phase. The concentration‐dependent selectivity of water partitioning in the self‐assembly of double hydrophilic block copolymers is unique and could be specific to zwitterionic block copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…Since the local hydration efficiency of the charges in the zwitterions is independent on the zwitterion species, water is involved in each phase at the high concentration stage. [ 34 ] However, once the water content is above the water capacity of the PSB4 phase, water is subjected to partition selectively to the PCB2 phase. The concentration‐dependent selectivity of water partitioning in the self‐assembly of double hydrophilic block copolymers is unique and could be specific to zwitterionic block copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…73 The variance in conformation between the atoms centered on phosphorus in PC lipid headgroup and the atoms centered on nitrogen in CP lipid headgroup results in differences in the spatial rotation degrees and entropy change (ΔS) of the headgroups. 74 Kobayashi et al showed that phosphoric acid groups had stronger hydrogen bond associations with water molecules. Thus, each CP headgroup in poly(2-methacryloyloxyethyl choline phosphate) (PMCP) could tightly bind 11 water molecules.…”
Section: Ligand-conjugated Lipidsmentioning
confidence: 99%
“…In comparison, each PC headgroup in poly(2methacryloyloxyethyl phosphorylcholine) (PMPC) binds 9 water molecules, indicating that CP liposomes could form a tighter and thicker hydration layer than PC liposomes. 74 Attributing to the increased thickness of the hydration layer, CP liposomes exhibit better antiprotein adsorption and antibacterial property than PC liposomes. 71 In addition, the maximum drug loading content of CP liposomes could reach 17.6%, 71 and the minimum particle size of drug unloaded CP liposomes could reach 30 nm, which may be related to the conformation of the CP headgroup and the compact hydration layer.…”
Section: Ligand-conjugated Lipidsmentioning
confidence: 99%
“…94 The hydration state and biocompatibility of these polymers can be tuned by controlling the side chain spacing 94,114,139–141 and changing the chemical structure of the side chains. 142–167…”
Section: Polymers From Monocyclic Alkenesmentioning
confidence: 99%